2013
DOI: 10.1016/j.gynor.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Uterine corpus metastasis in stage IA1 squamous carcinoma of the cervix

Abstract: HighlightsTreatment of stage 1A1 cancer of the cervix often involves preservation of the corpus.Rarely metastasis to the corpus can occur in these cases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The possible characteristics that increase metastasis include age > 45 years, histological type of squamous cell carcinoma, uterine involvement and lymphatic invasion [ 10 ]. It was seldom reported that early-stage CSCC could also metastasize to the ovary [ 9 – 14 ], although Shimada M et al suggested that FIGO stage was not significant in patients with ovarian metastasis [ 4 ]. In those reports, most ovarian metastases in CSCC were in early stage IA2–IIB [ 4 , 10 , 11 , 13 ], and only one case was in stage IA1, with one carcinoma in situ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The possible characteristics that increase metastasis include age > 45 years, histological type of squamous cell carcinoma, uterine involvement and lymphatic invasion [ 10 ]. It was seldom reported that early-stage CSCC could also metastasize to the ovary [ 9 – 14 ], although Shimada M et al suggested that FIGO stage was not significant in patients with ovarian metastasis [ 4 ]. In those reports, most ovarian metastases in CSCC were in early stage IA2–IIB [ 4 , 10 , 11 , 13 ], and only one case was in stage IA1, with one carcinoma in situ.…”
Section: Discussionmentioning
confidence: 99%
“…However, those metastasis focuses were tiny and superficial. One case had only minimal foci in the endometrium, the fallopian and ovary were normal, and there was no evidence of LVSI [ 14 ]. Other cases of ovarian metastasis could only be observed under a microscope on the ovarian surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation